Predictive Factors of Lamivudine Treatment Success in a Hepatitis B Virus-Infected Pediatric Cohort: A 10-Year Study. (2012) - Yousef, Yasmine; Béland, Kathie; Mas, Emmanuel; Lapierre, Pascal; Bouron Dal Soglio, Dorothée; Alvarez, Fernando
Abstract : BACKGROUND: Hepatitis B virus (HBV) infections are responsible for the development of chronic hepatitis in 400 million people worldwide. Currently, no consensus exists as to when treatment should be initiated for pediatric patients. OBJECTIVES: To evaluate the risks and predictive factors of success of lamivudine treatment in children with chronic, active HBV infection. METHODS: Forty-three children (22 male, median age 9.6 years) chronically infected with HBV and treated between 1998 and 2008 at CHU Ste-Justine (Montreal, Quebec) were included in the present chart review study. Inclusion criteria were detectable hepatitis B surface antigen and hepatitis B e antigen (HBeAg), minimum serum alanine aminotransferase (ALT) level of two times the upper limit of normal and detectable serum HBV DNA for at least three months. Patients received lamivudine for a minimum of six months (median 14 months). Genotyping was performed. RESULTS: Lamivudine treatment was effective in 35% of cases (15 of 43) and overall virological response (during or after treatment) was achieved in 51% of patients. Three patients harboured suspected lamivudine-resistant mutations and five progressed to HBeAg-chronic HBV. Predictive factors for success of treatment were: younger age at beginning of treatment (P=0.05), elevated ALT levels throughout treatment duration (P=0.003) and loss of HBeAg during treatment (P=0.016). Asian origin did not affect treatment success or spontaneous viral control during follow-up. HBV genotype did not influence treatment success. CONCLUSIONS: Lamivudine treatment in a carefully selected cohort of HBV patients demonstrated a good rate of success and low incidence of mutation. Younger age at the beginning of treatment and high ALT levels during treatment predicted a positive outcome.